Comparison of real-ear insertion gains in Japanese-speaking individuals wearing hearing aids with DSLv5 and NAL-NL2. Issue 1 (February 2021) - Furuki, Shogo; Sano, Hajime; Kurioka, Takaomi; Ogiwara, Atsuko; Nakagawa, Takahito; Inoue, Rie; Umehara, Sachie; Hara, Yuki; Suzuki, Keiko; Yamashita, Taku
Abstract: Objective: We used real-ear insertion gain (REIG), with the international speech test signal (ISTS), to evaluate the amplifying characteristics of hearing aids, set for patients who have been wearing such aids for a long time in a stable manner. We further compared this to the target values of the DSLv5 and NAL-NL2 methods. Methods: The subjects were adults with moderate sensorineural hearing loss. We examined 40 ears in 25 individuals (15 people wearing hearing aids in both ears and ten people wearing aid in only one ear). Fit assessments were performed based on the speech performance-intensity functions and tolerance of environmental noise, and the ears studied were categorized as either ears with sufficient benefit or ears with insufficient benefit. Additionally, we evaluated the REIG for international speech test signals at 65-dB and 80-dB sound pressure level (SPL). We compared the REIG and target values for voice input at 65-dB and 80-dB SPL, calculated from the DSLv5 and NAL-NL2 methods. Results: Among the 40 ears, 34 received sufficient benefit and six received an insufficient benefit from hearing aids. The REIG for ISTS at 65-dB in the sufficient benefit ears, at frequencies of 1, 000 Hz and 2, 000 Hz, were similar to the target values of NAL-NL2 and DSLv5 but were significantly lower at 250 Hz, 500 Hz, and 4, 000 Hz frequencies. The compression ratio of REIG for sufficient benefit ears was similar to that of DSLv5. The REIG for ISTS at 65-dB in the insufficient benefit ears was smaller than that in the sufficient benefit ears at frequencies of 2, 000 Hz and 4, 000 Hz. Conclusion: This study suggested that the target values of NAL-NL2 and DSLv5 are appropriate, even for Japanese-speaking individuals, at mid-pitch sounds. Although it is necessary to investigate the necessity for low-pitch and high-pitch gains further in the future, this study provides meaningful data regarding the amplifying characteristics in Japanese-speaking individuals who have been wearing hearing aids in a stable manner.